The degradation of American history - Harlan, David (David Craig) (ACLS Humanities E-Book., 1997)
American historical writing has traditionally been one of our primary forms of moral reflection. However, David Harlan argues that in the disillusionment following the 1960s, history abandoned its redemptive potential and took up the methodology of the social sciences. In this provocative new book, Harlan describes the reasons for this turn to objectivity and professionalism, explains why it failed, and examines the emergence of a New Traditionalism in American historical writing. Part One, "The Legacy of the Sixties," describes the impact of literary theory in the 1970s and beyond.